Modelling of grain breakage of in a vertical rice mill based on DEM simulation combining particle replacement model. (March 2022) - Zeng, Yong; Mao, Biqi; Jia, Fuguo; Han, Yanlong; Li, Gengrun
Abstract : Rice milling is a common practice for the post-harvest processing of rice grains. However, the production of broken rice during the milling is an inevitable and universal problem. Thus, it is important to understand the grain breakage mechanisms for improving the final quality of milled rice. The work aims to propose a development of numerical methodology combining discrete element method (DEM) and particle replacement model (PRM) for modelling grain breakage in a vertical rice mill. Using dimensional analysis and fracture mechanics, a mass-specific threshold dissipation energy was determined that, if exceeded, allowed the contribution to grain breakage to be determined. Based on the continuum damage mechanics, the damage accumulation coefficient describing the amenability of a material to sustain damage prior to breakage was obtained. Then a mathematical model characterising particle strength weakening when subjected to repeated low-energy loading was established. Furthermore, the breakage criterion that judges whether rice grain breaks was also set up. On the basis of the numerical method established, the number and size of the post breakage daughter particles was determined from rice milling tests. The required material parameters were determined by single breakage and fracture when subjected to repeated loading tests. Finally, the required number of impacts before a particle breaks and the subsequent breakage ratio during milling predicted from the simulation were shown to be consistent with experimental results. The proposed numerical method is useful for providing theoretical guidance to further clarify the breakage mechanisms that occur in a rice mill. Graphical abstract: Image 1 Highlights: A numerical method based on DEM and PRM is used to simulate rice grain breakage. Mass-specific threshold dissipation energy judging effective collision is applied. Damage accumulation coefficient describes strength weakening by repeated stressing. Proposed method is validated by comparing simulated and experimental results.